Tata Kelola SDM Pemerintah dalam Pengelolaan Website OPD: Studi Kasus Diskominfo Kota Serang - Nandita Anggraini; Laeli Nur Khanifah; Umina Marsyaro; Laras Destriana; Noni Nabilatun Nufus (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the human resource governance of the Serang City Government in managing the website of the Regional Apparatus Organization (OPD), which plays a crucial role in public information disclosure. The urgency of this research arose due to the inactivity of many OPD websites, hindering transparency and accountability. This study uses Sedarmayanti's Good Governance theory as the basis for analysis, encompassing participation, transparency, accountability, effectiveness, and law enforcement. The research method used was qualitative with a phenomenological approach to explore the experiences of website managers and the public. The results indicate that the main obstacles lie in human resource capacity, multiple tasks, minimal training, and weak coordination.